2019
DOI: 10.13005/bpj/1753
|View full text |Cite
|
Sign up to set email alerts
|

Role of Thermography in Assessment of Mygenous Joint Disorder

Abstract: The main objective of this review was to identity the usage of thermography in diagnosis of orofacial pain. Thermography is a method of measurement of skin temperature distribution on the body over a given period of time. Hence using the skin temperature, an advantages result can be obtained in identifying diseased condition in orofacial region. This article highlights the basics of thermography as a diagnostic tool in dentistry in identifying orofacial pain. PUBMED and Google Scholar were searched to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In accordance with the results of photographs in this patient, it was found that there was a difference of up to 0.5°C, which may be used to identify the disturbance in the TMJ. [ 8 9 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the results of photographs in this patient, it was found that there was a difference of up to 0.5°C, which may be used to identify the disturbance in the TMJ. [ 8 9 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…Fathima et al highlighted the importance of thermography which is used as a diagnostic tool in dentistry to evaluate the OFP. They also indicated that there is an increased facial temperature found in OFP patients than the asymptomatic patients (Fathima & Dharman, 2019). The validation of thermography in the assessment of facial disorders reported in the literature has motivated us to develop an orofacial assessment tool based on facial thermography.…”
mentioning
confidence: 96%